Lacunary strong almost A-convergence with respect to a sequence of Orlicz functions - Esi, Ayhan; Gokhan, Ayseguel (Eudoxus Press, Llc, 2010)
The purpose of this paper is to introduce and study some sequence spaces which are defined by combining the concepts of a sequence of Orlicz functions, infinite matrix and lacunary convergence. We also examine some topological properties of these sequence spaces and establish some elemantary connections between them.
Keywords: Lacunary sequence; Orlicz function; almost convergence